Prognostic value of composite inflammatory markers in patients with chronic obstructive pulmonary disease: A retrospective cohort study based on the MIMIC-IV database - Xingxing Liu; Yikun Guo; Wensheng Qi (PLoS ONE, 2025)
Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory lung disease, and inflammation plays a key role in the pathogenesis of COPD. The aim of this study is to investigate the association between systemic immune inflammation index (SII), systemic inflammatory response index (SIRI),pan-immune inflammation value (PIV), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) and all-cause mortality in patients with chronic obstructive pulmonary disease (COPD), and to evaluate the effect of composite inflammatory markers on the prognosis of COPD patients. We obtained data on COPD patients from the Medical Information Mart for Intensive Care (MIMIC) -IV database and divided patients into four groups based on quartiles of baseline levels of inflammatory markers, The primary outcomes were in-hospital and ICU mortality. We comprehensively explored the association between composite inflammatory markers and mortality in patients with COPD using restricted cubic splints (RCS), COX proportional hazards regression models, Kaplan-Meier curves, receiver operating characteristic (ROC), and subgroup analyses. A total of 1234 COPD patients were included in this study. RCS results showed that SII, SIRI, PLR, PIV and NLR were positively and non-linearly correlated with the increased risk of in-hospital mortality in COPD patients. Multivariate COX regression analysis showed that compound inflammatory markers were independent risk factors for in-hospital mortality in COPD patients. The KM curve results showed that COPD patients with higher SII, SIRI, PLR and PIV had a significantly lower survival probability. 5 kinds of compound between inflammatory markers and mortality in patients with COPD is related to nonlinear correlation, can increase the risk of mortality in patients with COPD is a risk factor for the prognosis of patients with COPD, and may serve as potential biomarkers for clinical COPD risk stratification and treatment management in critical patients.